Journal bearing and internal leakage modelling for a novel vane compressor - Poh, Wai Chang (2018)
The global energy demand and consumption escalates and is expected to continue increasing over the years, especially in the air conditioning sector. Recently, a new compressor intended to be used for air conditioning system called the Novel Vane Compressor (NVC) was invented, and there is a need to investigate its viability and advantages over other types of compressors. This report presents the contribution of the journal bearing and internal leakage modelling for the NVC. The working chamber, journal bearing and internal leakage modelling of NVC was carried out using numerical simulation with R1234yf as the working fluid. Furthermore, the internal leakage studies were also conducted and simplified using computational fluid dynamics (CFD), and its feasibility was discussed. The numerical simulation suggested that at the reference operating speed of 3000 rpm, the longer journal bearing radius and length were found to induce more power loss due to larger lubricant oil area. The numerical simulation was simplified by the CFD simulation results and the rotor end face leakage was found to be more than 80% of the total internal leakage of NVC, which was the major contributor to the internal leakage of NVC.